THE USE OF COHESIVE DEVICES IN ASIAN ENGLISH AS FOREIGN LANGUAGE (EFL) JOURNAL - Yenni Arif Rahman (Yayasan Akrab Pekanbaru, 2018)
The study provides an empirical analysis on the use of cohesive devices in EFL asian journal written by non-native english researchers from asian countries. Data for the study were 20 journals collected from 4 asian efl journals. Halliday and Hassan seminal work of â€œCohesion in Englishâ€ provides a comprehensive taxonomy of cohesive devices and Dooley and Levinsohn monograf gives the thorough examples how to analyse cohesive devices in the text. Of 566 cohesive devices found in the samples, 204 (36%) were lexical cohesion and 174 (30.7%) were conjunctions which are relatively in balance of both usage in the journal. However, the use of repetition as a part of lexical cohesion dominates the whole lexical cohesion by 92% (189) which is interpreted as the overuse of cohesive device of this type. Key Words: Cohesive Devices, EFL Journal, Overuse.